Noch einmal zu-- : kleine Schriften von Stefan Radt zu seinem 75. Geburtstag - Radt, S. L. (Mnemosyne, Supplements, 2002)
This volume contains the collected articles of the Groningen Professor of Ancient Greek, Stefan Radt, and a survey of his publications. These articles, which show great philological acumen, are of considerable importance for the study of ancient Greek literature and linguistics. This collection of distuingished papers will prove a valuable and useful acquisition for libraries and students of ancient Greek.